A concepção de história em Flávio Josefo : "o judeu de Roma" - Nascimento, Samuel Martins (2008)
In the second half of I b.C. century. Roman domination had been consolidated, territorially and politically in the Mediterranean. The Empire, since the Augustus' epoch (63 B.C. to 14 A.D.), included almost all Mediterranean and Oriental lands, becoming Rome in a commercial and financial centre. The difticulties to manage the conquested lands became frequent. Specially the Judea province, that was being affected by interior conflicts, suffered directiy the intervention that resulted on the war between Romans and Jewish. Flavius Josephus, the "Jewish of Rome", lived this only moment in the history of the Jews. The result of his active participation on the conflicts is found in Josephus' .The Jewish War. Our objective on analyzing the narrative of Jewish-roman war presented by Josephus is reflecting about his history conception and its insertion on the Old historiography context.